Behavioural effects of a community‐oriented setting‐based intervention for prevention of childhood obesity in eight European countries. Main results from the IDEFICS study. (December 2015) - De Bourdeaudhuij, I.; Verbestel, V.; De Henauw, S.; Maes, L.; Huybrechts, I.; Mårild, S.; Eiben, G.; Moreno, L. A.; Barba, G.; Kovács, É.; Konstabel, K.; Tornaritis, M.; et al.
Summary: Objective: The objective of this paper is to evaluate the behavioural effects, as reported by the parents of the participating boys and girls, of the IDEFICS (Identification and prevention of Dietary‐ and lifestyle‐induced health EFfects In Children and infantS) intervention. Methods: The effectiveness of the IDEFICS intervention was evaluated through a cluster‐controlled trial in eight European countries (control and intervention communities in each country) including more than 16, 000 children. The 2‐ to 9.9‐year‐old children in the intervention group were exposed to a culturally adapted intervention that aimed to prevent childhood obesity through the community, schools/kindergartens and family. Parents completed questionnaires to measure water, soft drink and fruit juice intake; fruit and vegetable intake; daily TV viewing and other sedentary behaviours; daily physical activity levels and strengthening of the parent–child relationships at baseline and follow‐up (2 years later). Mixed models with an additional random effect for country were used to account for the clustered study design, and results were stratified by sex. Results: The pan‐European analysis revealed no significant time by condition interaction effects, neither for boys nor girls, i.e. the analysis revealed no intervention effects on the behaviours of the IDEFICS children as reported by their parents ( F  = 0.0 to 3.3, all p  > 0.05). Also very few significances were found in the country‐specific analyses. Positive intervention effects were only found for sport club participation in Swedish boys, for screen time in weekends for Spanish boys and for TV viewing in Belgian girls. Conclusion: Although no expected intervention effects as reported by the parents on diet, physical activity and sedentary behaviours could be shown for the overall IDEFICS cohort, a few favourable intervention effects were found on specific behaviours in some individual countries. More in‐depth analyses of the process evaluation data are needed to obtain more insight into the relationship between the level of exposure to the intervention and its effect. © 2015 World Obesity